Renal impairment among acute hospital admissions in a rural Ethiopian hospital. Issue 2 (20th January 2013) - Riley, Stephen; Diro, Ermias; Batchelor, Peter; Abebe, Alula; Amsalu, Ashenafi; Tadesse, Yewondwossen; Williams, John; Phillips, Aled O
<x xml:space="preserve">Abstract</x> This paper describes the spectrum of acute kidney injury (AKI) in a general hospital in rural Ethiopia. Most patients were young, had pre‐renal AKI, and the mortality was no different from those with no AKI. Despite limitations, the study brings out differences with AKI seen in developed World.